2011
DOI: 10.1039/c0cp01890b
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of switching properties and excited-state dynamics of fulgides by structural modifications

Abstract: The ultrafast photo-induced dynamics of the E-isomers of four selected photochromic fulgides with distinct structural motifs have been elucidated by femtosecond broadband transient absorption spectroscopy in n-hexane as solvent. E→C and E→Z isomerisations, respectively, with time constants of ∼0.12 ± 0.02 ps and ∼0.34 ± 0.03 ps taking place in parallel were found for derivatives with a methyl substituent at the central hexatriene (HT) unit. In contrast, fulgides with increased steric constraints by an iso-prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 65 publications
3
51
0
Order By: Relevance
“…An explanation for these different photochemical properties caused by steric or electronic differences can be derived from femtosecond timeresolved transient absorption spectroscopy. [10] In particular, the time-resolved measurements revealed that the photo-induced ring-closure reactions are considerably faster in the cases of 13 and 14 (τ ≈ 50 fs) compared with 12 and 15 (τ ≈ 110 and 140 fs, respectively). Thus, the molecule-specific dynamics in the excited electronic states appear to play decisive roles.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…An explanation for these different photochemical properties caused by steric or electronic differences can be derived from femtosecond timeresolved transient absorption spectroscopy. [10] In particular, the time-resolved measurements revealed that the photo-induced ring-closure reactions are considerably faster in the cases of 13 and 14 (τ ≈ 50 fs) compared with 12 and 15 (τ ≈ 110 and 140 fs, respectively). Thus, the molecule-specific dynamics in the excited electronic states appear to play decisive roles.…”
Section: Resultsmentioning
confidence: 98%
“…The ratio between rotamers is approximately 6:1, which is in excellent agreement with the calculated fraction of the E α conformer of 82 % and 18 % of the E β conformer. [10] Based on the knowledge of rotational barriers in the furylfulgide, it is likely that the E α Ǟ E β conversion, which becomes visible in this furylfulgide analogue, is due to increased steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furan [12,21] 333-364 472-519 96-98 % 0.18 Thiophene [21,22,23] 272-339 414-532 51-92 % 0.13 Pyrrole [24] 364-389 584-642 30-60 % 0.20 Benzofuran [25,26,27,28] 330-387 488-511 43 % 0.17 Benzothiophene [10,29,30] Irradiation wavelengths within the visible light range are desirable in various photopharmacological studies, as light in this range does not greatly interfere with cellular function. [32] A bathochromic shift in the absorption spectra of fulgimides was achieved by the incorporation of an electron-rich heteroaromatic moiety [33][34][35] or a dicyanomethylene-modified anhydride.…”
Section: Photochromism and Heteroaromatic Influencesmentioning
confidence: 99%
“…Tsinberg and coworkers researched the structural and spectral properties of indolylfulgides with different substituents by applying DFT and TDDFT methods. Siewertsen et al also revealed the importance of electronic and steric effect to the ring‐opening process and excited‐state dynamics of several structurally modified furylfulgides. They considered that the study of electronic and structural modification may be used to improve the photoswitching dynamic of fulgides.…”
Section: Introductionmentioning
confidence: 99%